Digital Transformation as a Catalyst for SMEs Productivity and Profitability in the Digital Era - Titis Sri Wulan; Reni; Rezty Arizta Putri; Dewi Agustina Solihin (Journal of Economic Education and Entrepreneurship Studies, 2024)
The issue in research regarding the impact of digital transformation on SME productivity and profitability often relates to the gap in access to technology. This study aims to analyze the influence of digital transformation on the productivity and profitability of Small and Medium Enterprises (SMEs). Using a qualitative literature review approach, the research explores various previous studies and compares their results to understand how digital technology can help SMEs improve operational efficiency and competitiveness in the global market. Based on previous findings, it was discovered that the adoption of technologies such as e-commerce, cloud-based inventory management, and digital marketing can increase SME productivity by up to 30% and profitability by an average of 35%. However, SMEs in Indonesia still face significant challenges, including limited technological infrastructure and low digital literacy. In addressing the challenges of the Fourth Industrial Revolution, support from the government and the private sector is crucial, particularly in providing digital training and access to technological infrastructure. This research also adopts the Theory of Technological Innovation, Resource-Based Theory, and Transaction Cost Economics Theory to understand the factors influencing digital transformation in SMEs. In conclusion, although there are many challenges in the digitalization process of SMEs, technology adoption can have a significant positive impact on productivity and profitability if supported by appropriate policies and infrastructure.